Study of Wear Properties of Jute/Banana Fibres Reinforced Molybdenum disulphide Modified Epoxy Composites. (2017) - Deepak, P.; Sivaraman, H.; Vimal, R.; Badrinarayanan, S.; Vignesh Kumar, R.
Abstract: With the increasing use of composites in various industrial applications, due to their excellent physical and chemical properties they made themselves more sustainable in the market. In this row, the wear properties of the composites were of interest for researchers over these years because of their excellent tribological properties. Over a period, an extensive research on the wear properties of various polymer matrix and metal matrix composites were carried out with different reinforcements. Epoxy resin matrix, eventhough have a moderate wear properties, it was chosen because of its high thermal stability which made its utilization in many tribological applications influenced by heat other than friction, possible. Herein, molybdenum disulphide was added to the epoxy resin at various weight fractions of 5%, 10% and 15% to increase the wear properties of the composites. Also a standard composite without modification was formed to study and compare the modification in various properties. The composite samples were studied for its wear, tensile, flexural and impact properties. The micrography of the worn surfaces of various samples formed was studied using the scanning electron microscopy.